Analisis Nilai-Nilai Pendidikan Islam dalam Film Titip Surat untuk Tuhan (2024) Karya Karsono Hadi - Sabina Nurul Azizah (Lembaga Yasin AlSys, 2026)
Studies on film as a medium for Islamic education have been widely conducted, yet research that specifically examines the representation of Islamic educational values encompassing akidah (creed), ibadah (worship), and akhlak (morality) in contemporary Indonesian films remains relatively limited. This study aimed to analyze the Islamic educational values represented in the film Titip Surat untuk Tuhan directed by Karsono Hadi. It employed a qualitative approach with a content analysis design, using Titip Surat untuk Tuhan as the research object selected through purposive sampling based on the relevance of its religious theme and social context. Data were collected through documentation by closely examining scenes, dialogues, and character behaviors that embody Islamic educational values, and were then analyzed using qualitative content analysis through the stages of data reduction, data display, and conclusion drawing. The findings show that Titip Surat untuk Tuhan comprehensively represents Islamic educational values, with a dominance of moral values reflected in attitudes of patience, sincerity, responsibility, and compassion, followed by creedal values manifested in belief and submission to Allah SWT’s decrees, as well as worship values expressed through both ritual and non-ritual acts of worship in the characters’ daily lives. These findings broaden the understanding of film’s role as a medium for the contextual and applicative internalization of Islamic values and underscore the importance of utilizing film as an alternative medium for Islamic Religious Education that is oriented toward character formation. The implications of this study include a theoretical contribution to the literature on media-based Islamic education and practical implications for educators in integrating religious films into the learning process, as well as opening avenues for further research on the effectiveness of religious films in shaping audience attitudes and behavior through reception studies or mixed-methods approaches.